Cell-Mediated and Humoral Immunity to Herpesviruses During and After Herpes Zoster Infections - Sørensen, Ole S. (1980)
The influence of herpes zoster virus infection on cell-mediated and humoral immunity to varicella-zoster virus (VZV), cytomegalovirus, and herpes simplex virus (HSV) was followed in 17 zoster patients from the first week to 6 months after start of eruptions. The clinical responses were registered and correlated to the immune responses. A significant depression in blast transformation on stimulation of lymphocytes with all three antigens was found on days 1 to 5 compared with transformations later after zoster eruptions and compared with controls. Phytohemagglutinin exhibited the same stimulation in the different groups and controls. No significant differences in interferon production in the various groups and controls were found on stimulation with the VZV and HSV antigens. All zoster patients became seropositive by complement fixation to VZV a few days after start of the zoster eruption. Two zoster patients showed a fourfold rise in complement fixation antibodies to HSV. Three patients had changes in complement fixation titers to cytomegalovirus, which could indicate new infection or reactivation of infection with this virus. A significant lower transformation index to VZV was found during the first 9 days in zoster patients with fever compared with patients without fever. The relevance of this observation is discussed in relation to a previous similar observation from our group.